PENGARUH DISTRIBUSI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIANPADA MARKETPLACE SHOPEE DI KABUPATEN KUTAI BARAT - Zulkifli; Reslianty Rachim (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2022)
This study aims to determine: the effect of distribution and promotion on the purchasing decision variables at the Shopee Indonesia Marketplace in West Kutai Regency. The sampling technique used the slovin formula with a sample of 100 respondents. The data collection technique uses an online questionnaire through the google form program, the data presented is data obtained from the results of respondents' answers which are processed using the SPSS version 20 calculation tool and analyze the value of multiple linear regression., Distribution, and Promotion. The results of this study indicate that the distribution variable has a significant positive effect, and promotion has a significant positive result and is the most dominant. Then in the F (simultaneous) test, the Fcount results are 59,246. while the results of Ftable in the distribution table with an error rate of 5% is 2.11, then Fcount>Ftable (59.246>2.11). This explains that the distribution and promotion variables simultaneously affect the purchase decision.